Urban Growth and Its Aggregate Implications - Duranton, Gilles; Puga, Diego (Econometrica, 2023)
We develop an urban growth model where human capital spillovers foster entrepreneurship and learning in heterogeneous cities. Incumbent residents limit city expansion through planning regulations so that commuting and housing costs do not outweigh productivity gains from agglomeration. The model builds on strong microfoundations, matches key regularities at the city and economy‐wide levels, and generates novel predictions for which we provide evidence. It can be quantified by relying on few parameters and gives us a basis to estimate them. We examine counterfactuals relaxing planning regulations or constraining city growth to assess the effect of cities on economic growth and aggregate output.